Pengembangan Infrastruktur Sumber Air untuk Kebutuhan Peternakan dalam Mendukung Program Ketahanan Pangan di Desa Tambong - Shofiyah, Qurrotus; Naris Wari, Wahyu; Melati Nurita Sandi, Dora (Politeknik Negeri Jember, 2026)
Water availability is a key factor in the sustainability of small-scale livestock farming. Tambong Village, Kabat District, Banyuwangi Regency, faces limited access to water for livestock needs, particularly during the dry season, as well as low community knowledge regarding water supply and distribution technologies. This community service program aims to develop efficient water source infrastructure and enhance community capacity in managing livestock water supply. The methods employed include site surveys and preliminary studies, technical planning, construction of shallow wells with gravity-based distribution systems, and training and socialization on water supply technology. The results indicate that the water infrastructure—consisting of a dug well, storage tank, piping network, and electrical system—has been successfully constructed and operates properly. Evaluation results show that the community’s level of understanding reached 85.17%, categorized as very good. This program contributes to improving livestock productivity and supports food security programs at the village level.